Validity of Lesson Plan Based on Multiple Intelligences for Learning Mathematics in Yunior High School Students - Kristanto, Vigih Hery; Rahajeng, Resty (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
The purpose of this study was to determine the validity of multiple intelligences based lesson plans for mathematics learning in junior high school students. Research method with qualitative and quantitative research methods. The results of the qualitative research obtained are a description of the validity of multiple intelligence-based lesson plans for learning mathematics in students. While quantitative research results from the scores obtained in the validity test. The data collection instrument used was in the form of a questionnaire to test the level and lesson plan that included in it. The validation guideline used consists of two types, namely guidelines for validating linguistic aspects and guidelines for validating aspects of the substance. Criteria for practicality and effectiveness of a learning tool which in this study is devoted to lesson plans, is measured based on the results of the draft trial. This validation guide is given to two expert validators, the first validator is a validator with the linguistic expertise field and the second validator is a validator of mathematical experts. Validators with linguistic expertise are used to determine the validity of linguistic aspects, while validators of the field of mathematical expertise are used to determine the validity of aspects of the substance. The results showed that the validity of linguistic aspects was 3.35 and the validity of the substance aspect (content) was 3.82, so it could be concluded that the lesson plan that had been prepared based on multiple intelligences for mathematics learning in junior high school students was valid based on linguistic aspects and aspects of substance.